AMPHIBIAN SPECIES DIVERSITY IN PROHIBITION FOREST AREA OF KENEGERIAN RUMBIO COSTUMARY KAMPAR SUB DISTRICT KAMPAR REGENCY - Wirdayati Irham; Defri Yoza; M. Mardhiansyah (Jurnal Ilmu Ilmu Kehutanan, 2017)
Amphibian is one of ecosystem component, as ecology or economy. Research about amphibian at Indonesia is very limited. Prohibition Forest Area of Kenegerian Rumbio Kampar Sub District Kampar Regency is one of conservation forest area had important animal to developed such as amphibian, but research about amphibian is not many yet. This research aim is for knowing amphibian species diversity in Prohibition Forest Area of Kenegerian Rumbio Kampar Sub District Kampar Regency. This research done at September-October 2016. The method that has been using is Visual Encounter Survey (VES) and made Pit Fall trap method. Amphibian species diversity that successful found are 71 individuals and 10 species. That species are Bufo melanostictus and Bufo quardriporcatus from Bufonidae family, Kaloula pulchra and Microhyla palmipes from microhylidae family, Fejervarya limnocharis, Hylarana glandulosa, Rana erythraea, Rana hosii, Rana ingeri and Rana nicobarienensis from Ranidae family. Aquatic habitat diversity index is 1,68 mean middle category, arboreal habitat is 1,25 mean low category and teresterial habitat is 1,60 mean middle category.